Second-order hydrodynamic effects on the response of three semisubmersible floating offshore wind turbines - Zhang, Lixian; Shi, Wei; Karimirad, Madjid; Michailides, Constantine; Jiang, Zhiyu (My University, 2020)
Floating structures have become the most feasible solution for supporting wind turbines when offshore wind project move to deeper water. In this paper, a hydrodynamic analysis of three different semisubmersible floating offshore wind turbines is carried out including second-order hydrodynamic effects. The three examined platforms are V-shaped semisubmersible, Braceless semisubmersible and OC4-DeepCwind semisubmersible and are used to support the NREL 5 MW reference wind turbine. The main objective of the present study is to investigate and compare the hydrodynamic response of the three different semisubmersible floaters in two water depths (100 m, and 200 m) under different load conditions. The effects of second-order wave loads on the platform motions and mooring tension are discussed and compared by using different methods including Newman's approximation and the full QTF (Quadratic transfer function) method. The drag effect on the structure motion response is also discussed in this paper. The comparison presented is based on statistical values and response spectra of floating platform motions as well as mooring tensions. The results show that the dynamic response of semisubmersible FOWTs (floating offshore wind turbines) is overestimated when ignoring the Morison drag effect on the columns of the semisubmersible FOWT. The second-order difference wave loads can excite the resonance of motion especially for the platform-pitch motion, which could cause structural failures. The full QTF method should be used to calculate the second-order wave force to better simulate the realistic dynamic response of semisubmersible FOWTs.
Keywords: Hydrodynamic loads; Newman's approximation; Quadratic transfer function; Second-order wave loads; Semisubmersible floating wind turbines